RHETORIC OF RULE: ULUGH BEG'S IMAGE IN SEKKAKI'S PANEGYRIC POETRY - Aynur, Hatice (Univ Science & Technology China-USTC, 2025)
Ulugh Beg (r. 1447-1449) occupies a unique position at the crossroads of science, governance, and literary culture, embodying the ideal of a philosopher-king in Timurid history. This study examines his patronage of poetry and engagement with literary traditions, drawing upon sources such as Majalis al-Nafa is (Assemblies of Distinguished Men) by 'Ali Shir Nawa i, Tadhkirat al-Shu ara (Memoirs of the Poets) by Dawlatshah Samarqandi, and the qasidas composed in his honor. Particular attention is given to qasidas by Sekkaki and others, which construct an idealized vision of kingship rooted in justice, cosmic harmony, and intellectual authority. By situating Ulugh Beg within a broader tradition of poetic praise and intellectual patronage, this research re-evaluates his legacy, arguing that his cultural contributions were as integral to his reign as his scientific achievements.
Keywords: Ulugh Beg; Sekkaki; literary patronage; qasida poetry; poetic praise; philosopher-king; intellectual legacy; cultural patronage; Astronomy & Astrophysics